New firm startups - Davidsson, Per. (Northampton, Mass. : Edward Elgar Pub., 2006)
It includes the qualitative and quantitative empirical research, which addresses both the antecedents and outcomes of new firm startups on different levels of analysis and provides insights into the process of new firm creation.
Overview -- Environment -- Individual -- Venture -- Process -- Outcomes.
Includes bibliographical references and index.
uaj 30/04/13
Loans
Keywords: New business enterprises; Entrepreneurship